The Influence of Management Knowledge, Employee Attitudes, Work Discipline through Decision Making on Occupational Health and Safety Management at PT Indonesia Comnets Plus - Amiruddin Al Hakim; Faisal Marzuki; Ivan Yulivan (Syntax Corporation Indonesia, 2022)
This study aims to determine and analyze management knowledge, employee attitudes, work discipline through decision making on MK3 at PT Indonesia Comnets Plus. In this study, there was a sample population taken from field workers totaling 98 workers, all of these workers were pulling engineering workers, fiber optic cable installations. The sample selection technique used in the study was saturated sampling where the entire population was sampled. The data analysis technique used is path analysis and hypothesis testing in this study using the partial test (t test) and the coefficient of determination test using the SPSS program. The results obtained from the data analysis of this study explain that there is a positive influence on Management Knowledge, Employee Attitudes, Work Discipline through Decision Making on Health and Safety Management after the research is used as a mediating variable.